2018
DOI: 10.3390/su10093264
|View full text |Cite
|
Sign up to set email alerts
|

Harmony in Diversity: Can the One Belt One Road Initiative Promote China’s Outward Foreign Direct Investment?

Abstract: This paper investigates the effect of the One Belt One Road (OBOR) initiative on China's outward foreign direct investment (OFDI) using a dataset of all host countries for the period of 2010-2015. The employed econometric technique combines a difference-in-differences estimator with matching techniques. The results show that China's OFDI in OBOR countries is about 40% higher than in non-OBOR countries. After the initiative, the OFDI from China increases by 46.2% in OBOR countries. However, after controlling fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 58 publications
4
68
0
1
Order By: Relevance
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
“…As Table 1 shown, we collected data from the six groups of stakeholders and then we placed them into five categories: None or few (0-20), not too much (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), neutral (41-60), partial (61-80), and very much (81-100). Among the 2563 responses related to the DAC, 62 people (2.4%) realized that the Afghan Government has no or few DACs to influence the development process of the Aynak Copper Mine, and 524 (20.4%) considered that there is not too much the DAC of the Afghan Government can do with the development of the Aynak Copper Mine.…”
Section: Variable Definitionsmentioning
confidence: 99%
“…Z. Liu, Wang, Sonn, and Chen (2018) examine the structure and changes in trade relations networks with the development of the BRI [6]. Kang, Peng, Zhu, and Pan (2018) investigate the influence of the BRI on China's outward foreign direct investment [7]. These investigations show the external economic environment of a region under transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The motives and the purpose of the "Belt and Road" initiatives reduced the resource-seeking motivation and boosted the market-seeking motivation of China's OFDI [3]. Promoting economic integration in a large geographical coverage and economic size through the "Belt and Road" has emerged an important new economic point of view and it also contributes to the development of the world [4].…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia's ambition to become the "Global Maritime Fulcrum" will be in line with the interests of the "Belt and Road" program, which has both direct and indirect implications and impacts on economic interests between China and Indonesia [10]. In fact, Chinese investments are mostly in the maritime silk road countries [3]. Leitao discovered that there is a positive correlation between FDI (Foreign Direct Investment) and bilateral trade promoting the economic growth in host countries [11].…”
Section: Introductionmentioning
confidence: 99%